2010
DOI: 10.1007/s12072-010-9215-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of small hepatocellular carcinoma with intravenous pegylated liposomal doxorubicin

Abstract: Purpose Synergy between radiofrequency ablation (RFA) and chemotherapy was demonstrated for liver malignancy. We assess the efficacy of intravenous pegylated liposomal doxorubicin (PLD) for RFA in patients with small hepatocellular carcinoma (HCC). Methods This study was designed as a non-randomized control trial. Patients received either PLD (20 mg) intravenously before RFA, or standard RFA alone. Computed tomography was performed immediately and 4 weeks after RFA to obtain ablative diameter, area and volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…RFA-PEI offered a significant survival advantage over RFA alone for patients with tumors 3.1–5 cm in diameter but not for those with tumors equal to or less than 3.0 cm in diameter or for those with tumors 5.1–7 cm in diameter. Moreover, some reports have suggested that RFA combined with injection of cytotoxic drugs improves the efficacy, although this remains to be proved [30]. Combination of different locoregional therapies is a simple, easy way to improve prognosis.…”
Section: Combination With Peimentioning
confidence: 99%
“…RFA-PEI offered a significant survival advantage over RFA alone for patients with tumors 3.1–5 cm in diameter but not for those with tumors equal to or less than 3.0 cm in diameter or for those with tumors 5.1–7 cm in diameter. Moreover, some reports have suggested that RFA combined with injection of cytotoxic drugs improves the efficacy, although this remains to be proved [30]. Combination of different locoregional therapies is a simple, easy way to improve prognosis.…”
Section: Combination With Peimentioning
confidence: 99%